Phytochemical Analysis by LC-HRMS and Antibacterial Activity Of the Ethanol Extract of Sengkuang (Dracontomelon dao (Blanco) Merr. & Rofe) - Ratih Dewi Dwiyanti; Anny Thuraidah; Nurlailah Nurlailah (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Dracontomelon dao (Blanco) Merr. & Rofe is one of the medicinal plants for the community. This study aims to analyze the ethanol extract of Sengkuang (Dracontomelon dao (Blanco) Merr. & Rofe) using the LC-HRMS Phytochemical Test and determine its antibacterial activity. Leaf Dracontomelon dao (Blanco) Merr. & Rofe originates from Hulu Sungai Utara, South Kalimantan, Indonesia, macerated with 96% ethanol. Antibacterial test by diffusion was carried out using the well method. LC-HRMS (Liquid Chromatography - High-Resolution Mass Spectrometry) test using the Instrument Thermo Scientific™ Dionex™ Ultimate 3000 RSLCnano UHPLC coupled with Thermo Scientific™ Q Exactive™ High-Resolution Mass Spectrometer. The content of chemical compounds from the ethanol extract, namely flavonoids 125.5 ± 0.433 mgEQ/g, alkaloids (%) 33.945 ± 0.781, saponins (%) 33.093 ± 0.755, tannins (mg/ml) 0.069 ± 0.003, the highest content was triterpenoids 669.8 ± 2,000(mg/ml). The best inhibition of E coli growth with the largest inhibition zone was 24 mm at a 500 mg/ml concentration. The active compounds contained in the leaves of Dracontomelon dao (Blanco) Merr. & Rolfe are quercetin-3β-D-glucoside, anacardic acid, D-glucosamine, azelaic acid, choline, astragalin, quercetin, luteolin, syringic acid. The active ingredient of the ethanol extract of Sengkuang (Dracontomelon dao (Blanco) Merr. & Rofe) has the potential as an antibacterial and anti-inflammatory that can be added to pharmaceutical preparations. Keywords: Dracontomelon dao (Blanco) Merr. & Rofe; Phytochemical Analysis; Liquid Chromatography - High-Resolution Mass Spectrometry